Biodiesel production from non-edible plant oils. Issue 2 (March 2016) - Demirbas, Ayhan; Bafail, Abdullah; Ahmad, Waqar; Sheikh, Manzoor
Biodiesel is an alternative to petroleum-based fuels derived from a variety of feedstocks, including vegetable oils, animal fats, and waste cooking oil. At present, biodiesel is mainly produced from conventionally grown edible oils such as soybean, rapeseed, sunflower, and palm. The cost of biodiesel is the main obstacle to commercialization of the product. Biodiesel produced from edible oils is currently not economically feasible. On the other hand, extensive use of edible oils for biodiesel production may lead to food crisis. These problems can be solved by using low-cost feedstocks such as non-edible oils and waste cooking oils for biodiesel production. This paper reviews numerous options of non-edible oils as the substantial feedstocks, biodiesel processing, and effect of different parameters on production of biodiesel.